Are we teaching our students what they need to know about ageing? Results from the National Survey of Undergraduate Teaching in Ageing and Geriatric Medicine - Gordon, Adam; Blundell, Adrian G.; Gladman, John R.F.; Masud, Tahir (Oxford University Press, 2010)
Introduction - Learning about ageing and the appropriate management of older patients is important for all doctors. This survey set out to evaluate what medical undergraduates in the UK are taught about ageing and geriatric medicine and how this teaching is delivered.